1999
DOI: 10.1006/dbio.1998.9190
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine-Mediated Apoptosis in Reproductive Tract Development

Abstract: In mammalian development, the signaling pathways that couple extracellular death signals with the apoptotic machinery are still poorly understood. We chose to examine Müllerian duct regression in the developing reproductive tract as a possible model of apoptosis during morphogenesis. The TGFbeta-like hormone, Müllerian inhibiting substance (MIS), initiates regression of the Müllerian duct or female reproductive tract anlagen; this event is essential for proper male sexual differentiation and occurs between emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…The expression of WT1 in the Mü llerian duct indicates that WT1 also might have a direct impact on Mü llerian duct regression. Interestingly, the AMH receptor was not found to be expressed in the epithelium of the Müllerian duct, but only in the surrounding interstitium and it was demonstrated that paracrine factors are involved in apoptosis of the Mü llerian ducts (Roberts et al 1999, Teixeira et al 2001. Since WT1 is known to play a role in apoptosis, it can be suggested that it might be implicated in the cellular crosstalk of Mü llerian duct regression (Menke et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of WT1 in the Mü llerian duct indicates that WT1 also might have a direct impact on Mü llerian duct regression. Interestingly, the AMH receptor was not found to be expressed in the epithelium of the Müllerian duct, but only in the surrounding interstitium and it was demonstrated that paracrine factors are involved in apoptosis of the Mü llerian ducts (Roberts et al 1999, Teixeira et al 2001. Since WT1 is known to play a role in apoptosis, it can be suggested that it might be implicated in the cellular crosstalk of Mü llerian duct regression (Menke et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is well described that AMH causes regression of the Müllerian duct by inducing cellular apoptosis (Roberts et al 1999). It is therefore interesting to speculate as to why the high concentrations in small follicles are not similarly damaging.…”
Section: Function Of Amh In the Normal Ovarymentioning
confidence: 96%
“…The MIS type I receptor has not been identified; however, bone morphogenic protein 1a is a strong candidate to be this receptor (5). Interaction between MIS and its receptor initiates a signal that ultimately causes regression of the mullerian ducts through apoptosis by a paracrine mechanism (6). Mutations in MIS or its type II receptor cause the human male sexual abnormalities, persistent mullerian duct syndrome and pseudohermaphroditism (7), and deletion of MIS or the MISRII also results in development of pseudohermaphroditism in mice (8,9).…”
mentioning
confidence: 99%